THE CAPABILITY OF LOCAL GOVERNMENT IN SAGO DEVELOPMENT: EFFORTS TO SUPPORT FOOD SECURITY IN THE REGENCY OF MERANTI ISLANDS - Rafi, M.; Ardiansyah, Ardiansyah; Purnomo, Eko Priyo; Handoko, Tito; Rahmat, Al Fauzi (CosmoGov: Jurnal Ilmu Pemerintahan, 2021)
Government efforts to support food security have been made through various potentials in the agricultural sector, such as sago development as a locally-based alternative food source. However, the facts show that sago can only be used as a second staple food and requires adequate local government capacity in its development. This study uses a qualitative method with a literature study approach. Data collection techniques used are documentation techniques in journals, proceedings, books, government websites, and online news related to various government strategies in developing sago. The results showed that the Meranti Islands Government had socialized the "One Day With Sago" program in knowledge and skills dimensions. However, due to insufficiently accommodated socialization, this program was less effective in changing the surrounding communitys lifestyle. Second, local governments ability in the technical system dimension is already running well; increased sago production shows this. Third, in the managerial system dimension, the local government has designated Meranti as a sago cluster and supports the sago development program budgeted through central, provincial, and district funds. Fourth, in the dimensions of values and norms, every organization that handles agricultural affairs has a good understanding of the sago development policys direction and objectives in the Meranti Islands.gb777